Pope John XXIII. - Richards, Norman (Chicago : Childrens Press, 1969)
The life of the Italian peasant who became Pope and instituted many reforms within the Catholic Church including a movement to unite Christian churches.
Bibliography: p. 92-93.
Keywords: John - XXIII, - Pope, - 1881-1963 - Juve; John - XXIII, - Pope, - 1881-1963.; Popes - Biography - Juvenile literature; Popes